Penggunaan Beton Plastis pada Dinding Halang Tubuh Bendung Proyek Bendungan Jlantah - Adhi, Bagas Wahyu; Markawie, Markawie (Lambung Mangkurat University Press, 2024)
The foundation is a very important part of a structure that is not protected by air such as sediment. Basic foundation repairs aim to ensure that the soil stress that arises as a result of the dam's own weight, air pressure, earthquake forces and acting loads does not exceed the carrying capacity of the dam foundation soil at the bottom or on the left and right banks of the dam. In the Jlantah Dam Construction Project there were problems related to the dam foundation. Repairs to the Jlantah Dam foundation were originally designed using curtain grouting, but from the results of grouting tests on the riverbed the results were not able to reach the required airtightness (Lugeon) value. Considering that alluvial deposition and strongly weathered rock layers are still quite porous, it is necessary to repair the foundation specifically using a cut-off wall or diaphragm wall. The purpose of using a diaphragm wall is to strengthen the foundation when the body bends. The method used in making plastic concrete is laboratory testing to obtain results that comply with standards. The conclusion obtained from plastic concrete on barrier walls is in accordance with applicable standards.